Cultivating Teacher's Christian Worldview in Integrating Faith and Learning: Case Study in Christian School East Java and Papua - Oki Hermawati; Lita Patricia Lunanta; Benny Benny; Silviana Fatmajanti S.; Richard Richard (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2024)
Cultivating a Christian worldview in Christian teachers is an important endeavor that must be pursued in Christian schools. This is related to how a Christian teacher applies integrating faith and learning in schools. The application of faith and learning requires a truly Christian worldview from a Christian teacher. The method used in this research is a case study in Christian schools in East Java and Papua, where efforts to develop a Christian worldview are a necessity during efforts to achieve integrated learning with the Christian faith. The results of the efforts to develop can be seen from the perception of Christian teachers who are increasingly sharp and understand holistically through a Christian worldview and understand the application of the integration of faith and learning in the context of Christian schools.